SOSIALISASI PEMANFAATAN MARKETPLACE DALAM MEMPERLUAS JARINGAN PASAR DI UMKM JARINGAN WIRAUSAHA JAWARA - Silviyani, Yuli Anita; Risthi, Alyssa (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The micro, small, and medium enterprise (MSME) sector faces various problems such as declining sales, capital, hampered distribution, and raw material difficulties. MSMEs must also change their marketing orientation, especially in today's modern era. Many MSMEs are turning to e-commerce to increase sales, but this is not supported by the ability of MSMEs, who tend to be low in using technology. This community service aims to provide understanding and skills for JAWARA MSMEs regarding the use of marketplaces as a means of selling and promoting products effectively and efficiently. They also provide assistance in utilizing internet-based marketplaces as a means of selling products and analyzing the use of social media in attracting customers and increasing consumers. The result of this activity is an understanding of partners regarding marketing through marketplaces and promotions through social media independently.